Feasibility and preliminary clinical tolerability of low‐field MRI‐guided prostate biopsy. Issue 7 (19th February 2023) - Sze, Christina; Singh, Zorawar; Punyala, Ananth; Satya, Poorvi; Sadinski, Molly; Narayan, Ramkrishnan; Nacev, Aleksander; Kumar, Dinesh; Adams, John; Nicholas, Kathryn; Margolis, Daniel; Chughtai, Bilal
Abstract: Objective: We evaluate the clinical feasibility of a portable, low‐field magnetic resonance imaging (MRI) system for prostate cancer (PCa) biopsy. Methods: A retrospective analysis of men who underwent a 12‐core systematic transrectal ultrasound‐guided prostate biopsy (SB) and a low‐field MRI guided transperineal targeted biopsy (MRI‐TB). Comparison of the detection of clinically significant PCa (csPCa) (Gleason Grade [GG] ≥ 2) by SB and low field MRI‐TB, stratified by Prostate Imaging Reporting & Data System (PI‐RADS) score, prostate volume, and prostate serum antigen (PSA) was performed. Results: A total of 39 men underwent both the MRI‐TB and SB biopsy. Median (interquartile range [IQR]) age was 69.0 (61.5−73) years, body mass index (BMI) was 28.9 kg/m 2 (25.3–34.3), prostate volume was 46.5 cc (32−72.7), and PSA was 9.5 ng/ml (5.5−13.2). The majority (64.4%) of patients had PI‐RADS ≥ 4 lesions and 25% of lesions were anterior on pre‐biopsy MRII. Cancer detection rate (CDR) was greatest when combining SB and MRI‐TB (64.1%). MRI‐TB detected 74.3% (29/39) cancers. Of which, 53.8% (21/39) were csPCa while SB detected 42.5% (17/39) csPCa ( p  = 0.21). In 32.5% (13/39) of cases, MRI‐TB upstaged the final diagnosis, compared to 15% (6/39) of cases in which SB upstaged the final diagnosis ( p  = 0.11). Conclusion: Low‐field MRI‐TB is clinically feasible. Although future studies on the accuracy of MRI‐TB system are needed, the initial CDR is comparable to those seen with fusion‐based prostate biopsies. A transperineal and targeted approach may be beneficial in patients with higher BMI and anterior lesions.